2009
DOI: 10.1055/s-0028-1109374
|View full text |Cite
|
Sign up to set email alerts
|

Spontane Visusbesserung bei amblyopen Erwachsenen nach Funktionsverlust des Führungsauges?

Abstract: In addition to new ways of assessing treatment compliance and quality of life, knowledge about the opinion of the treating personnel concerning various aspects of a disease may lead to more evidence-based treatment. In amblyopic patients, the inclusion of certain details into the documentation (type and separation of the optotypes, optical correction) may be essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…30 Cases have been reported in the scientific literature of spontaneous visual improvement in the severely amblyopic eyes in adults following visual loss in the good eye. [31][32][33] Therefore, no patient should be denied amblyopia therapy because of his/her age.…”
Section: Discussionmentioning
confidence: 99%
“…30 Cases have been reported in the scientific literature of spontaneous visual improvement in the severely amblyopic eyes in adults following visual loss in the good eye. [31][32][33] Therefore, no patient should be denied amblyopia therapy because of his/her age.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown significant visual improvement in the blind eye only after losing vision in the better eye. 1–3 Still, the underlying mechanisms are unknown.…”
mentioning
confidence: 99%